As dimensões da gestão no processo de organização escolar : significados para a equipe gestora - Gomes, Adriano Sabino (2017)
The historical process has revealed that the school administration model receives influence of capitalism, reinforcing its keeping, as a hegemonic model of society. However , from the decade 1970, with the rise of sociologyc approach, the models administrative of positivist influence reveived cristicism with arising of pedagogy of conflict antagonistic to the pedagogy of consensus, new managment models have emerged with a view to overcoming administrative models that aim only the maintaing existing order. Based on economic dimensions, pedagogical, political and cultural that comprises the multidimensional paradigm of education adminstration developed by Benno Sander, this study aims to bring the meaning that the school director, the pedagogical coordinator and school secretary gives the organizational dimensions of the school. The methodological option was the qualitative approach in the dialectical perspective. The research was developed with nine persons that integrating the management team of two state schools. The informations was acquired through the interview half structured and research documentar (PPP, Internal Rules, Meeting Minutes, Action Plans of school director, pedagocical coordenator and relugations of SEDUC). Although democratic management has been implemented in the state of Mato Grosso in 1998, the research developed on the basis of the last two warrants of school directors. The result of reseach could show us that the school admininstration is based only on the economic and pedagogical dimensions which invalidate the use of the multidimensional administration paradigma of education, like a model surpass of the administration developed by the managment team at the school. Among other factors, the school struture show to be responsible the organization process based only this two dimensions. In spite of the pedagycal dimension are presente in organization process, a administration based on pedagogical effectiveness. It add to the strengthening of the burden economic, disregarding the cultural relevence of the administrative aspects of education implicate with the social transformation.